Identifikasi Drug Related Problems (DRPs) Pada Pasien Pediatri Pneumonia Komunitas di Instalasi Rawat Inap RSD Madani Provinsi Sulawesi Tengah: Identification of Drug Related Problems In Pediatric Patients With Community Acquired Pneumonia at Madani Hospital Central Sulawesi - Putu Maharani Ajeng Astiti; Alwiyah Mukaddas; Safarudin Atho Illah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Drug Related Problems (DRPs) are events or circumstances involving drug therapy that actually or potentially interfere with desired health outcomes. DRPs may occur in the treatment of various diseases such as community acquired pneumonia (CAP). This study aims to determine the percentage of DRPs in pediatric inpatients with CAP. This is a descriptive and observational study design with prospective data conducted in November 2015 until February 2016 at Madani Hospital, Central Sulawesi. The results obtained from 28 patients showed that incidences of DRPs categories of inappropriate drug is 1 event (1,7%), inappropriate drug combination 35 events (58,3%), drugs dose too low 18 events (30%), drugs dose too high 6 events (10%), and no indication for drug 0 event (0%).